The integration of interactive whiteboard for collaborative learning in Greek nursery schools - Papageorgiou, Vasiliki (2015)
Abstract Interactive whiteboards (IWBs) have become increasingly available in nursery and primary schools. Their potential benefits for the development of collaborative learning practices are valuable for young students learning experience. However, little is known about how they are integrated by teachers into classrooms for collaborative learning and their influence on students’ learning experiences. A qualitative multiple case-study approach was used to investigate the way IWBs are currently used for collaborative learning by two Greek nursery school teachers. The focus was placed upon the way teachers perceive IWB affordances when planning collaborative learning activities. Students’ interactions generated by IWB and teacher mediation were also explored. Two learning activities with IWB were designed by each teacher. The methods used included informal conversational interviews with teachers before activity implementation, lesson observations and follow-up interviews with teachers and groups of students. The study showed that teachers created multimodal learning environments which aim to engage collective thinking and student collaboration. IWBs were used as a shared working space for the externalisation of student thought through the co-creation of digital artefacts. Another perspective of IWB was its use as a space for the connection of collaborative group work with the whole-class participation. IWB integration into school classrooms reinforced teacher’s role as a supporter of students’ collaborative interactions. Students’ interactions differed widely, but were deemed satisfactory. A range of factors including but not limited to the nature of the task, student collaborative skills and relationships together with teacher’s support influenced their interactions. Several issues including difficulty in classroom orchestration, technical issues and difficulty in representations appeared to change the initial planning and teachers’ visions for students’ collaboration. This study suggests that the use of the IWB for collaborative learning in early education settings can reinforce students’ interactions. To maximise the potential positive interactions, the teachers should combine appropriately IWB affordances as underpinned by the notion of sociocultural learning theory and be active supporters of students’ collaboration. Further research is needed to investigate the way IWB is used by teachers for collaboration in a greater number of classroom settings to better understand influence on students’ learning and inform pedagogical practices. Keywords: Collaborative learning, Interactive Whiteboards (IWBs), nursery schools, technology integration, pedagogical approaches.